Assessment Instruments of Mathematics Learning Outcomes for Grade IV Elementary School Students - Yantini, Ni Putu Mia Ari; Suarjana, I Made; Sumantri, Made (Jurnal Ilmiah Sekolah Dasar, 2021)
Teachers still do not pay attention to the minimum standards or basic competencies that must be achieved by students, so that in making assessment questions it is not according to students' abilities and the achievement of basic competencies from the subject matter being studied. This study aims to develop an instrument for assessing mathematics learning outcomes for fourth-grade elementary school students. This type of research is development research. The model used in this study is using the ADDIE (analyze), (design), (development), (implementation), (evaluation) model. The subjects used were 2 mathematicians/experts and 30 students as respondents. The techniques used in collecting data are observation, interviews, document recording, tests. The research results will be analyzed for validity and reliability. Instruments that have been designed to collect data are then tested first to find out the validity of the instrument. The results showed that the number of valid items was 18 items that were declared valid and 2 items that were not valid. After that, a reliability test is carried out. In this reliability test, it can be done if the items are declared valid. Instrument reliability can be tested using the Kuder Richardson 20 (KR-20) formula with the help of the Microsoft Office Excel application. The results of the calculation of instrument reliability obtained r11 = 0.82 has a "very high" consistency. Thus, the instrument for assessing mathematics learning outcomes for fourth-grade elementary school students is valid and appropriate to be used as an instrument for assessing mathematics learning outcomes. This research implies that the instrument can be used as a guide for developing other assessment instruments and can help teachers understand how to make good questions so that learning objectives can be achieved optimally.